Iwi’gara, The Kinship of Plants and People: American Indian Ethnobotanical Traditions and Science. By Enrique Salm’on. 2020. Timber Press, Portland, OR. 245 pp. - Pierotti, Raymond (Ethnobiology Letters, 2022)
This is a book review and soes not have an abstract.